Molecular analysis of genetic differences between Mycobacterium bovis BCG and virulent M. bovis. - Mahairas, G G (1996)
The live attenuated bacillus Calmette-Guérin (BCG) vaccine for the prevention of disease associated with Mycobacterium tuberculosis was derived from the closely related virulent tubercle bacillus, Mycobacterium bovis. Although the BCG vaccine has been one of the most widely used vaccines in the world for over 40 years, the genetic basis of BCG's attenuation has never been elucidated. We employed subtractive genomic hybridization to identify genetic differences between virulent M. bovis and M. tuberculosis and avirulent BCG. Three distinct genomic regions of difference (designated RD1 to RD3) were found to be deleted from BCG, and the precise junctions and DNA sequence of each deletion were determined. RD3, a 9.3-kb genomic segment present in virulent laboratory strains of M. bovis and M. tuberculosis, was absent from BCG and 84% of virulent clinical isolates. RD2, a 10.7-kb DNA segment containing a novel repetitive element and the previously identified mpt-64 gene, was conserved in all virulent laboratory and clinical tubercle bacilli tested and was deleted only from substrains derived from the original BCG Pasteur strain after 1925. Thus, the RD2 deletion occurred after the original derivation of BCG. RD1, a 9.5-kb DNA segment found to be deleted from all BCG substrains, was conserved in all virulent laboratory and clinical isolates of M. bovis and M. tuberculosis tested. The reintroduction of RD1 into BCG repressed the expression of at least 10 proteins and resulted in a protein expression profile almost identical to that of virulent M. bovis and M. tuberculosis, as determined by two-dimensional gel electrophoresis. These data indicate a role for RD1 in the regulation of multiple genetic loci, suggesting that the loss of virulence by BCG is due to a regulatory mutation. These findings may be applicable to the rational design of a new attenuated tuberculosis vaccine and the development of new diagnostic tests to distinguish BCG vaccination from tuberculosis infection.